AB0203 The role of estrogens on the production of IL-21 in patients with systemic lupus erythematosus. (23rd January 2014) - Lee, J.; Jung, S.M.; Lee, J.H.; Kim, J.M.; Cho, M.-L.; Kwok, S.-K.; Ju, J.H.; Park, K.-S.; Park, S.-H.; Kim, H.-Y.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease in which various organs and tissues are damaged through abnormal immune responses mediated by tissue-binding autoantibodies. Though, the exact pathogenic mechanism is not clearly elucidated, estrogens are thought to play an important role because over 90% of SLE patients are women. IL-21 is an important cytokine which is produced by T cells, especially Th17 and induces B cell activation. Thus, it has been suggested that IL-21 plays a critical role in the pathogenesis of autoimmune diseases. Objectives: We investigated the effect of estrogens on the production of IL-21 and subsequent B cell activation in SLE patients. Methods: Peripheral blood mononuclear cells (PBMCs) were obtained from peripheral blood of SLE patients and healthy controls. CD4+ T cells, non CD4+ T cells, B cells were isolated using micro beads. The expression of IL-21 and its receptors was assessed by ELISA (serum) and real time PCR (PBMCs, CD4+ cells). The level of immunoglobulin G secreted by activated B cells were measured with specific ELISA. Results: The expression of IL-21 and its receptors in serum, PBMC, and CD4+ T cells was higher in patients with SLE compared to healthy controls. The production of IL-21 was increased when the cells are stimulated with estrogen in dose- and time- dependent manners. IL-21 production was decreased in the presence of MAP kinase (MEK, p38, JNK) inhibitors. B cells of healthy controls showed an increased antibody production when they were co-cultured with estrogen-stimulated CD4+ T cells of patients with SLE. IL-21 antibodies suppressed the increased antibody production of the co-culture systems. Conclusions: This study revealed a possible role of estrogens in the pathogenesis of SLE. Estrogens increase the production of IL-21 by activating CD4+ T cells via MAP kinase dependent pathways in SLE patients. Disclosure of Interest: None Declared